Financial reporting dimensions of intangibles in the context of Islamic finance - Syed Jaafar Alhabshi, Syed Musa; Syed Agil, Sharifah Khadijah; Ahmed, Mezbah Uddin (IIUM Press, 2018)
Prior studies have identified that not all “intangibles” are reported as “intangible assets” in the statement of financial position. This particularly concerns the Islamic finance industry where intangibles are often used as underlying assets in structuring products. Accordingly, this research examines the unique Shari’ah requirements and the dichotomous views on the validity and permissibility of intangibles to be recognized as assets. As a result of an apparent need to re-examine the sufficiency of international financial reporting standards (IFRS/IAS) and the views of Shari’ah scholars on financial assets, the research is designed to analyse the sufficiency of IAS 38 Intangible Assets with reference to The Conceptual Framework for Financial Reporting of International Accounting Standards Board (IASB). For this purpose, an in-depth interview, two focus group discussions and a survey of target respondents from both academia and industry directly involved in reporting of Islamic financial servicesare carried out. From the engagement session with the Shari’ah scholars, the research has identified an alternative view of concern with reference to appropriate Shari’ah rulings to determine the permissibility and validity of intangible assets and its reporting implications. Whereas, a mixed response is observed in the survey in terms of clarity on accounting policy, treatment and disclosures with reference to the technicality of the standards as well as the peculiarity of the context in Islamic finance industry